Acrocalymma guizhouense sp. nov. (Acrocalymmaceae, Dothideomycetes) from soil in China - Shao, Qiu-Yu; Qi, Ying-Hua; Wang, Jing; Yang, Yan-Ming; Zhang, Zhi-Yuan; Chen, Wan-Hao; Liang, Jian-Dong; Liang, Zong-Qi; Han, Yan-Feng (Phytotaxa, 2022)
A new species of Acrocalymma, A. guizhouense, isolated from the rhizosphere soil of Perilla frutescens, is introduced. Morphological characteristics, culture characteristics on PDA, OA, MEA, and phylogenetic analyses based on multi-locus datasets (SSU + LSU + ITS) support the establishment of the new species. Morphologically, A. guizhouense is distinguished from other species of Acrocalymma in having narrow conidia with a width of 1.5-2.5 µm. Phylogenetically, A. guizhouense formed a separated subclade with well-supported (100 MLBS/1.00 BYPP) value, which confirmed the taxonomic placement in the genus Acrocalymma.